2021
DOI: 10.1002/jsfa.11536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin‐mediated photodynamic treatment on lipid degradation of oysters during refrigerated storage

Abstract: BACKGROUND Oyster's lipid degradation leads to a decrease in edible and nutritional value. Curcumin‐mediated photodynamic treatment (PDT) is an innovative non‐thermal technology, although evaluation of the oyster's lipid degradation has been scarce. In the present study, we investigated peroxide value, thiobarbituric acid reactive substance, triacylglycerol and free fatty acids to evaluate the effect of curcumin‐mediated PDT on lipid degradation of oysters during refrigerated storage. RESULTS The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Purine nucleoside phosphorylase (PNP) deaminates the hypoxanthine side, which is then oxidized by xanthine oxidase (XOD) to produce xanthine and finally uric acid (Cader et al, 2020). Purine content varies with enzyme activity, which has been confirmed by studies (Lu et al, 2021; Zhang et al, 2020). For this purpose, the activity of a key enzyme related to purine metabolism (5′‐NT, PNP, ADA, XOD) was determined in Figure 4.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Purine nucleoside phosphorylase (PNP) deaminates the hypoxanthine side, which is then oxidized by xanthine oxidase (XOD) to produce xanthine and finally uric acid (Cader et al, 2020). Purine content varies with enzyme activity, which has been confirmed by studies (Lu et al, 2021; Zhang et al, 2020). For this purpose, the activity of a key enzyme related to purine metabolism (5′‐NT, PNP, ADA, XOD) was determined in Figure 4.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the change of hypoxanthine con- (Cader et al, 2020). Purine content varies with enzyme activity, which has been confirmed by studies (Lu et al, 2021;Zhang et al, 2020). For this purpose, the activity of a key enzyme related to purine metabolism (5′-NT, PNP, ADA, XOD) was determined in Figure 4.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The decrease of Psychrilyobacter may be affected by the low lipid content in sea urchin gonads. Zhang et al (2021) reported that Psychrilyobacter was associated with lipid degradation.
Fig.
…”
Section: Resultsmentioning
confidence: 99%